Interaktive audiodramaer i byens rum - Kortbek, Karen Johanne (Peripeti, 2021)
Kortbek examines the interactive audio drama, AudioMove, invented and staged by »Teater Katapult« (Catapult Theatre) through discussing the concept of making the city ‘come alive’ through an interactive drama as well as the technological conditions for the participant’s experience.